دور العلاقات العامة في تحقيق الصورة الذهنية للمؤسسة - زيان شيماء; زيان نرجس (كلية العلوم الإجتماعية, 2022)
جاء دراستنا لتبرز دور العلاقات العامة في تحسين الصورة الذهنية، للمؤسسة العمومية الاستشفائية، واختارنا مؤسسة "حمادو حسين " بسيدي علي ولاية مستغانم كأحد أهم مؤسسة لإجراء دراستنا وتطبيقها عليها الأسباب التي دفعتنا لاختيار هذا الموضوع هي: الرغبة في التعرف على كيفية عمل جهاز العلاقات العامة في المؤسسة حيث قمنا بطرح التساؤل الرئيسي: ما هو دور العلاقات العامة في تحسين الصورة الذهنية واندرج تحت هذا التساؤل الرئيسي عدة تساؤلات فرعة منها. هل للعلاقات العامة دور في تحسين الصورة الذهنية للمؤسسة العمومية الاستشفائية؟ - - ما هي وسائل الاتصال التي تعتمد عليها إدارة العلاقات العامة للتواصل مع جماهيرها كما اعتمدنا على المنهج الوصفي باعتباره ومناسب لدراستنا، وقد تستخدم لكل من أداة ملاحظة ومقابلة واستمارة كأداة أساسية لجمع المعلومات والبيانات المتعلقة بالدراسة. كانت خطة بحثنا كالآتي :الاطار المنهجي ثم الاطار النظري، والذي كان حول العلاقات العامة والصورة الذهنية مفاهيم و وظائف أما الاطار التطبيقي كان عن دراسة ميدانية حاولنا من خلاله تقريب الواقع محاولة منا فهمه والوقوف على دور العلاقات العامة في تحسين الصورة الذهنية للمؤسسة وفي الأخير قمنا بتفريغ البيانات وتحليلها والتوصل إلى نتائج عامة للدراسة Study summary: Our study came to highlight the role of public relations in improving the mental image of the public hospital institution, and we chose the “Hamado Hussein” Foundation in Sidi Ali, Mostaganem state, as one of the most important institutions to conduct our study and apply it to it. The reasons that prompted us to choose this topic are: Desire to learn how the public relations apparatus works in the institution. Where we asked the main question: What is the role of public relations in improving the mental image Several subsidiary questions were included under this main question, including: Does public relations have a role in improving the mental image of the public hospital institution? - What are the means of communication that the Public Relations Department relies on to communicate with its audiences, as we relied on the descriptive approach as it is appropriate for our study, and it may be used for each of the observation tool, interview and form as a basic tool for collecting information and data related to the study. Our research plan was as follows: The methodological framework and then the theoretical framework, which was about public relations and mental image concepts and functions. As for the applied framework, it was about a field study, through which we tried to bring reality closer, trying to understand it and to stand on the role of public relations in improving the mental image of the institution. Finally, we extracted and analyzed the data and reached general results for the study.
دراسة ميدانية بالمؤسسة الاستشفائية العمومية الشهيد حمادو حسين سيدي علي مستغانم
Keywords: الصورة الذهنية-العلاقات العامة